P-233-Biodiversity of mucosa associated microbiome of Crohn's disease patients living in middle western São Paulo State, Brazil - Santos, Ana Carolina da Silva [UNESP]; Sassaki, Ligia Yukie [UNESP]; Romeiro, Fernando Gomes [UNESP]; Gomes, Luma [UNESP]; Rodrigues, Josias [UNESP] (Oxford University Press (OUP), 2013)
Background: The intestinal microbiome (IM) has extensively been studied in the search for a link of bacteria with the cause of Crohn`s disease (CD). The association might result from the action of a specific pathogen and/or an eventual imbalance in bacterial species composition of the gut. The innumerous virulence associated markers and strategies described for adherent and invasive Escherichia coli (AIEC) have made them putative candidate pathogens for CD. IM of CD patients shows dysbiosis, manifested by the proliferation of bacterial groups such as Enterobacteriaceae and reduction of others such as Lactobacillus and Bifidobacterium. The augmented bacterial population comprising of commensal and/or pathogenic organisms super stimulates the immune system, triggering the inflammatory reactions responsible for the clinical manifestations of the disease. Considering the role played by IM in CD and the multiple variables influencing its species composition, resulting in differences among populations, the objective of this study was to determine the bacterial biodiversity in the mucosa associated microbiome of CD patients from a population not previously subject to this analysis, living in the middle west region of Sao Paulo state. Methods: A total of 4 CD patients and 5 controls subjects attending the Botucatu Medical School of the Sao Paulo State University (UNESP) for routine colonoscopy and who signed an informed consent were included in the study. A number of 2 biopsies, one from the ileum and other from any part of the terminal colon, were taken from each subject and immediately frozen at -70[degrees]C until DNA purification. The bacterial biodiversity was assessed by next generation (ion torrent) sequencing of PCR amplicons of the ribosomal DNA 16S V6 region (16S V6 rDNA). The bacterial identification was performed at the genus level, by alignment of the generated DNA sequences with those available at the ribosomal database project (RDP) website. Results: The overall DNA sequence output was based on an average number of 526,427 reads per run, matching 50 bacterial genus 16SrDNA sequences available at the RDB website, and 22 non matching sequences. Over 95% of the sequences corresponded to taxa belonging to the major phyla: Firmicutes, Bacterioidetes, Proteobacteria and Actinobacteria. Irrespective of the intestinal site analyzed, no case-control differences could be observed in the prevalence of Actinobacteria and Firmicutes. The prevalence of Proteobacteria was higher (40%) in the biopsies of control subjects as compared to that of DC patients (16%). For Bacterioidetes, the higher prevalence was observed among DC patients (33% as opposed to 14,5% in controls). The significance for all comparisons considered a p value < 0,05 in a Chi2 test. No mucosal site specific differences could be observed in IM comparisons of CD and control subjects. Conclusions: The rise in the number of Bacterioidetes observed here among CD patients seems to be in agreement with most of studies published thus far. Yet, the reduction in the number of Proteobacteria along with an apparently unaltered population of Actinobacteria and Firmicutes, which include the so called "beneficial" organisms Bifidobacterium and Lactobacillus were rather surprising. These data suggest that the analyses on the role of IM in CD should consider the multiple variables that may influence its species composition.